6 - Choosing Heaven: Negotiating Modernity in Diverse Social Orders - Bialostocka, Olga (Africa Development, 2020)
Situated within the topic of geographical contexts of knowledge production, this article interrogates the youth policies of Kenya, Ghana and Tanzania to understand how they articulate the concepts of ‘tradition’ and ‘modernity’ in planning for youth development in their national socio-cultural settings. The focus is on each country’s approach to cultural transformation, in trying to divulge how the policymakers see the role of culture, both local and global, in young people’s lives, and articulate this notion in the policies to produce a politically desired alternative to Western modernity. The article goes on to discuss the extent to which ‘African modernity’ constructs are set out in these policy documents as attempts to ‘de-westernise’ the concept. It recognises Ghana’s approach as the most decolonial, for it distances the country’s cultural transformation process from the perceived universality of Western values. The article suggests that modernity, as an ‘imaginary pursuit’, becomes powerful only when one chooses to imagine it in the first place.